2022
DOI: 10.1002/aisy.202200081
|View full text |Cite
|
Sign up to set email alerts
|

Modular Origami Soft Robot with the Perception of Interaction Force and Body Configuration

Abstract: Bio‐inspired soft robots provide a promising solution for robots working in human‐centered scenarios and interacting with unstructured environments. However, the functional versatility and multimodal sensing of soft robots still need improvements. On one hand, the configuration of a soft robot is predefined during manufacturing; on the other hand, the multimodal perception of the deformable soft actuator is challenging. In this work, a reconfigurable and proprioceptive soft origami module is presented, where t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…For soft manipulation, many soft origami robots actuated by an air pump performed as a soft gripper to grab objects [163][164][165] with intelligent sensing functions. [166,167] In the field of machinery manufacturing, origami was employed to build transformable car wheels that showed a high weight-to-payload ratio. [168] Further, inspired by the folded morphology of biological wings, origami is a very good tool to develop small aircrafts for flight movements with retractable wings.…”
Section: D Origami Electrical Soft Robotsmentioning
confidence: 99%
“…For soft manipulation, many soft origami robots actuated by an air pump performed as a soft gripper to grab objects [163][164][165] with intelligent sensing functions. [166,167] In the field of machinery manufacturing, origami was employed to build transformable car wheels that showed a high weight-to-payload ratio. [168] Further, inspired by the folded morphology of biological wings, origami is a very good tool to develop small aircrafts for flight movements with retractable wings.…”
Section: D Origami Electrical Soft Robotsmentioning
confidence: 99%
“…Additionally, range sensing on deformable objects is subject to interference and misalignments between sensors as the actuators deform. Soft mechanical sensors can both be integrated directly into the robot body and provide accurate force and shape estimations ( Kim et al, 2021 ; Dorsey et al, 2022 ; Sun et al, 2022b ; Dong et al, 2022 ; Thuruthel et al, 2019 ; Huang et al, 2022 ; Wang et al, 2022 ). Improving mechanical sensor performance to achieve closed-loop control will be critical to meet future soft robotics sensing and control needs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some sensing origami soft actuators based on different perceptual mechanisms have been applied to underwater environments. [17,18] These studies have demonstrated that soft actuators can respond to external stimuli and achieve more functionality based on intelligent methods. Nevertheless, they lack a comprehensive perception system that can completely integrate and utilize sensors' nonlinear data in actual environments.…”
Section: Introductionmentioning
confidence: 99%